Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/smll.202002837
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofiber/Carbon Nanotube‐Based Bicontinuous Ion/Electron Conduction Networks for High‐Performance Aqueous Zn‐Ion Batteries

Abstract: Despite their potential as a next‐generation alternative to current state‐of‐the‐art lithium (Li)‐ion batteries, rechargeable aqueous zinc (Zn)‐ion batteries still lag in practical use due to their low energy density, sluggish redox kinetics, and limited cyclability. In sharp contrast to previous studies that have mostly focused on materials development, herein, a new electrode architecture strategy based on a 3D bicontinuous heterofibrous network scaffold (HNS) is presented. The HNS is an intermingled nanofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 44 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…The CNT@KMO@ GC displays the smallest bulk resistance (R bulk , the point that the high frequency region intersects the real axis) and charge transfer resistance (R ct , the diameter of the semicircle), verifying its highest electrical conductivity and electron-transfer kinetics. [32,33] This result further proves the highest electrical conductivity of CNT@KMO@GC among all the samples, indicating the best electrochemical performance.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…The CNT@KMO@ GC displays the smallest bulk resistance (R bulk , the point that the high frequency region intersects the real axis) and charge transfer resistance (R ct , the diameter of the semicircle), verifying its highest electrical conductivity and electron-transfer kinetics. [32,33] This result further proves the highest electrical conductivity of CNT@KMO@GC among all the samples, indicating the best electrochemical performance.…”
Section: Resultssupporting
confidence: 59%
“…The improvement of electrolyte wettability in CNT@KMO@GC facilitates the electrolyte into and out from the electrode, resulting in the enhanced electrochemical performance of CNT@KMO@GC. [32] The electrical conductivity of KMO, CNT@KMO, and CNT@KMO@GC was also studied. As shown in Figure 5b, the electrical conductivity of KMO, CNT@KMO, and CNT@KMO@GC is 0.06, 0.15, and 4.87 S cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This monotonous architecture often causes the inhomogenous distribution of cathode components, leading to sluggish electron/ion conduction in the through-thickness direction together with structural disruption upon exposure to mechanical deformation. [15][16][17][18][19] To date, a few studies have been reported on flexible LMBs, mainly focusing on the design of composite electrodes comprising porous carbon scaffolds, [20,21] carbon nanotubes, [13,22] and modified metal current collectors. [23,24] These works have shown improvements in electrochemical reversibility, redox Despite extensive studies on lithium-metal batteries (LMBs) that have garnered considerable attention as a promising high-energy-density system beyond current state-of-the-art lithium-ion batteries, their application to flexible power sources is staggering due to the difficulty in simultaneously achieving electrochemical sustainability and mechanical deformability.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanomaterials, such as cellulose nano bers (CNFs), cellulose nanocrystals (CNCs), 2,6,6tetramethylpiperidine-1-oxy-oxidized cellulose nano bers (TEMPO-CNFs), and other derivatives have received signi cant attention as a next-generation nanomaterial because of their abundancy, good biocompatibility, good chemical/physical properties, degradability, low-cost, large-scale production, and diverse use for composite materials (Dai et Kim et al 2020). Different treatment processes, which initiate degradation reactions, are used to break the glycosidic bonds in cellulose macromolecules to obtain cellulose nanoparticles with a onedimensional size ranging from 1-100 nm.…”
Section: Introductionmentioning
confidence: 99%